Effect of ultraviolet light treatment on microbiological safety and quality of fresh produce: An overview - Yemmireddy, Veerachandra; Adhikari, Achyut; Moreira, Juan (Frontiers in Nutrition, 2022)
Fresh and fresh-cut fruits and vegetables have been associated with several foodborne illness outbreaks. Although investigations from those outbreaks reported that the contamination with pathogenic microorganisms may occur at any point in the farm to fork continuum, effective control strategies are still being widely investigated. In that direction, the concept of hurdle technology involving a sequence of different interventions has been widely explored. Among those interventions, ultraviolet (UV) light alone or in combination with other treatments such as the use of organic acids or sanitizer solutions, has been found to be a promising approach to maintain the microbiological safety and quality of fresh and fresh-cut produce. Recent advances in using UV as a part of hurdle technology on the safety of fresh produce at different stages are presented here. Furthermore, this review discusses the mechanism of UV induced antimicrobial activity, factors that influence antimicrobial efficacy and its effect on produce. In addition, the challenges, and prospects of using UV irradiation as an intervention treatment were also discussed.